PERLINDUNGAN HUKUM BAGI KONSUMEN DALAM PERJANJIAN PEMBIAYAAN MULTIGUNA PADA APLIKASI KREDIVO - NIM. A1012161106, AGUNG RINALDI (Fakultas Hukum Universitas Tanjungpura, 2024)
AbstractThe Kredivo application is a financing service that allows users to buy the desired item in installments. When using the Kredivo application, a multipurpose financing agreement will arise. The focus of this research is legal protection for consumers/users of the Kredivo application in the multipurpose financing agreements contained therein. The aim of this research is to analyze legal protection for consumers in multipurpose financing agreements on the Kredivo application. The second objective of this research is to analyze the legal consequences for Kredivo application users in multipurpose financing agreements. The research method used is normative law, namely by examining existing library materials which are compiled and presented prescriptively, namely explaining the complete picture and describing and validating existing problems. In article 19 paragraph (1) of the Financial Services Authority Regulation Number 35/POJK.05/2018 concerning the Implementation of Financing Company Business, it is stated that